Protective effect of sildenafil citrate on contralateral testis injury after unilateral testicular torsion/detorsion - Yildiz, Hamit; Durmus, Ali Said; Simsek, Halil; Yaman, Mine (Elsevier Espana, 2011)
OBJECTIVES: This study was designed to investigate prevention of contralateral testicular injury with sildenafil citrate after unilateral testicular torsion/detorsion. METHODS: Thirty-seven adult male rats were divided into four groups: sham operated (group 1, n = 7), torsion/detorsion + saline (group 2, n = 10), torsion/detorsion + 0.7 mg of sildenafil citrate (group 3, n = 10) and torsion/detorsion + 1.4 mg of sildenafil citrate (group 4, n = 10). Unilateral testicular torsion was created by rotating the right testis 720 degrees in a clockwise direction for 2 h in other groups, except for group 1, which was served as sham group. After torsion (2 h) and detorsion (2 h) periods, rats were killed. RESULTS: The level of reduced glutathion (GSH) (p < 0.05) and the activities of catalase (p < 0.01) and glutathione peroxidase (p < 0.05) in the contralateral testis from group 2 were significantly lower and nitric oxide (NO) (p < 0.05) level in the contralateral testis were significantly higher than those of group 1. Administration of low-dose sildenafil citrate (group 3) prevented the increases in malondialdehyde and NO levels and decreases in glutathione peroxidase activities and GSH values induced by testicular torsion. However, administration of high-dose sildenafil citrate (group 4) had no effect on these testicular parameters (p > 0.05). Histopathological changes were detected in groups 2, 3 and 4. CONCLUSION: These results suggest that biochemically and histologically torsion/detorsion injury occurs in the contralateral testis following 2-h torsion and 2-h detorsion and that administration of low-dose sildenafil citrate before detorsion prevents ischemia/reperfusion cellular damage in testicular tissue.
Keywords: Testicular torsion; Ischemia-reperfusion damage; Sildenafil citrate; Rat